Democracy - Saward, Michael, 1960- (Cambridge, UK : Polity ; Malden, MA : Distributed in the USA by Blackwell Pub., 2003)
"Working through a series of compelling real and hypothetical cases, twentieth-century narratives of democracy and their roots, and major new challenges such as globalization and environmentalism, the book makes the ideal starting point both for students already curious and those needing to be enticed and provoked. It concludes with a snapshot and appraisal of the new theories of democracy that are making waves in the twentieth-first century, and invites informed speculation on the shape of the democracy of the future. Democracy includes an extensive glossary of types of democracy, as well as a guide to further reading."--Jacket.
Is this democracy? -- Narrating Democracy I -- Narrating Democracy II -- Five challenges -- Reinventing democracy.
Includes bibliographical references (pages 161-168) and index.